Evaluation of a strategy to incorporate reproductive biotechnologies into buffalo farming without affecting reproductive parameters of the herd: A Colombian case (2018)
ABSTRACT: Buffalo breeders need to improve buffalo production to satisfy the market needs, reproduction is one of the parameters to be improved specially if it is combined with reproductive biotechnologies. The aim of this paper is to show a Colombian Experience in which artificial insemination is introduced to the current management of a buffalo herd without affecting the reproductive parameters. It has been obtained a decrease of 26 days in the day open of the farm, pregnancy rates of the natural heat and fixed time artificial insemination are not statistically different and are similar to those reported in the literature. The feasibility of using AI in buffalo herds without affecting reproductive parameters is reported here and also allowing to get the benefits of artificial insemination to improve production.